Efektivitas Penggunaan Aplikasi Wordwall dalam Pembelajaran Daring (Online) Matematika pada Materi Bilangan Cacah Kelas 1 di MIN 2 Kota Tangerang Selatan - Nafia Wafiqni; Fanny Mestyana Putri (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2021)
The purpose of this study was to determine the effectiveness of the use of the Wordwall application in online mathematics learning on counting number 1 in MIN 2 South Tangerang and the effectiveness of using Wordwall media in the closing activity which was reviewed throgh test results (final test of all materials). The research used is a combination research by combining quantitative and qualitative techniques. With the subject of this research are 56 studens of class 1 MIN 2 South Tangerang. In this study, various instruments were used to collect data such as: (1) interviews to support the result of student response questionnaires (2) interviews to support the results of student response questionnaires (3) questions throgh the Wordwall media and test questions to see the effectiveness of using Wordwall media in online mathematict learning activities. The results of this study were (1) in the student response questionnaire using Wordwall media in the closing activities of online mathematics learning, counting numbers were very effective with an average questionnaire value of 32,3 (2) the results of the tests carried out by the students resulted in a percentage completeness of 88,04 and 75% of the number of students so that it has been declared effective.